Radio-frequency association of Efimov trimers - Lompe, Thomas; Ottenstein, Timo Bastian; Serwane, Friedhelm; Wenz, André Niklas; Zürn, Gerhard; Jochim, Selim (Science, 2010)
The quantum mechanical three-body problem is one of the fundamental challenges of few-body physics. When the two-body interactions become resonant, an infinite series of universal three-body bound states is predicted to occur, whose properties are determined by the strength of the two-body interactions. We used radio-frequency fields to associate Efimov trimers consisting of three distinguishable fermions. The measurements of their binding energy are consistent with theoretical predictions that include nonuniversal corrections.
Gesehen am 30.03.2023